67.2k views
2 votes
3a-b=-9 -3a-2b=0 solve by elimination

1 Answer

2 votes

a = –2 and b = 3

Solution:

Given equations are

3a – b = –9 – – – – (1)

–3a – 2b = 0 – – – – (2)

To solve these equations by elimination method.

Elimination method means eliminating one variable to find the other variable.

Add equation (1) with equation (2), we get

3a – b + (–3a – 2b) = –9 + 0

⇒ 3a – b – 3a – 2b = –9

Combine like terms together.

⇒ 3a – 3a – b – 2b = –9

⇒ 0 – 3b = –9

⇒ – 3b = –9

Divide by (–3) on both sides, we get

b = 3

Substitute b = 3 in equation (1), we get

(1) ⇒ 3a – b = –9

⇒ 3a – 3 = –9

Add 3 on both sides of the equation,

⇒ 3a = –6

Divide 3 on both sides of the equation

a = –2

Hence, a = –2 and b = 3.

User Piertoni
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.